Waste Management and the Administrative Evaluation of Resources for the Benefit of the Community. The Analysis of Methods for their Use - Skenderi, Bajame; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
Administrative and Support and Waste Management and Remediation Services sector comprises establishmentsperforming routine support activities for the day-to-day operations of other organizations. These essential activities are oftenundertaken in-house by establishments in many sectors of the economy. The establishments in this sector specialize in one ormore of these support activities and provide these services to clients in a variety of industries and, in some cases, tohouseholds. Activities performed include: office administration, hiring and placing of personnel, document preparation and similarclerical services, solicitation, collection, security and surveillance services, cleaning, and waste disposal services. This paperresearch provides information relating to employment and unemployment in waste management and remediation services. Whilemost data are obtained from employer or establishment surveys, information on industry unemployment comes from a nationalsurvey of households. The following tables present an overview of the industry including the number of jobs, the unemploymentrate of those previously employed in the industry, mass layoffs, data for occupations common to the industry, and projections ofoccupational employment change. We are gather information from Albanian projects and incentives on waste management. Whywaste management is still with problems in Albania? In this paper research we want to analyze the factors for promoting andrecycling the waste in Albania region.